Development and assessment of particular transmission-blocking malaria vaccines - Li, Y (2014)
Transmission-blocking vaccines (TBVs) target Plasmodium parasite sexual stages, aiming to block further development of the parasite within the mosquito host. Plasmodium falciparum zygote/ookinete surface protein Pfs25 is one of the leading TBV candidate antigens and antibodies against Pfs25 have been shown to exhibit complete transmission-blocking activity in pre-clinical studies. Phase 1 human clinical trials have revealed that Pfs25 was a poor immunogen in humans in the formulations tested and high titers of anti-Pfs25 antibodies are required to achieve good transmission-blocking activity in the ex vivo standard membrane feeding assay which measures the functional activity of the antibodies induced. Work in this thesis describes the production of recombinant monomeric Pfs25 protein, Pfs25 based particulate vaccines (Pfs25-IMX313 nanoparticle, Pfs25-HBsAg VLP and Pfs25-Qβ VLP) and a Pfs25-Pfs28 multivalent protein vaccine in the Pichia pastoris protein expression system. These proteins were tested in mice using protein-in-adjuvant formulations and their immunogenicity was assessed. Pfs25-IMX313 nanoparticle induced significantly higher anti-Pfs25 antibodies than monomeric Pfs25 and the antibodies had higher avidity and transmission-blocking activity. All of the candidate vaccines generated, except for Pfs25-HBsAg VLP, were immunogenic. The Pfs25-IMX313 nanoparticle induced the highest antibody response in mice followed by the Pfs25-Pfs28 multivalent protein and Pfs25-Qβ VLP.